2016
DOI: 10.1177/0013124516630602
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Educators’ and Student Teachers’ Beliefs About Preparation for Working With Families Including Those From Diverse Socioeconomic and Cultural Backgrounds

Abstract: This mixed-methods study examined teacher preparation for developing family partnerships. The attitudes and practices of teacher educators and the attitudes and experiences of student teachers were explored in focus groups, documents, and a survey instrument. Results indicated that although partnerships were considered important by faculty and students, both groups were concerned with the difficulties teachers may experience with parents. The subject university is committed to diversity and requires a field ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 30 publications
1
45
0
1
Order By: Relevance
“…These legislative mandates clearly point to the importance of teachers promoting parent involvement in early school experiences and this emphasis needs to be an intentional component of teacher preparation programs (Mitsch et al, 2020;Taylor & Kim, 2020). Therefore, as theoretical and empirical perspectives support the critical role of parents in students' success, pre-service teachers too must continue receiving training on ways to engage with parents (D'Haem & Griswold, 2017;Epstein & Sanders, 2006;Hoover-Dempsey, Walker, Jones, & Reed, 2002). In their work, Epstein and Sanders (2006) surveyed administrators in 161 teacher preparation programs and found that, although respondents agreed on the importance of involving families, few believed that graduating students were fully prepared to do so.…”
Section: Engaging Parents In Schoolsmentioning
confidence: 99%
See 4 more Smart Citations
“…These legislative mandates clearly point to the importance of teachers promoting parent involvement in early school experiences and this emphasis needs to be an intentional component of teacher preparation programs (Mitsch et al, 2020;Taylor & Kim, 2020). Therefore, as theoretical and empirical perspectives support the critical role of parents in students' success, pre-service teachers too must continue receiving training on ways to engage with parents (D'Haem & Griswold, 2017;Epstein & Sanders, 2006;Hoover-Dempsey, Walker, Jones, & Reed, 2002). In their work, Epstein and Sanders (2006) surveyed administrators in 161 teacher preparation programs and found that, although respondents agreed on the importance of involving families, few believed that graduating students were fully prepared to do so.…”
Section: Engaging Parents In Schoolsmentioning
confidence: 99%
“…In their work, Epstein and Sanders (2006) surveyed administrators in 161 teacher preparation programs and found that, although respondents agreed on the importance of involving families, few believed that graduating students were fully prepared to do so. Emphasizing the need for specific courses on school, family, and community partnerships, the benefits of family engagement in student academic and social success is highlighted (Delgado-Gaitan, 2007;Epstein, 2006;Epstein et al, 2018), and teacher educators are challenged to prepare future teachers for effective partnerships with families (D'Haem & Griswold, 2017). In particular, the lack of preparation for pre-service teachers on how to work with families has been highlighted as being problematic and despite some progress within initial teacher preparation programs, few pre-service teachers have access to full courses on how to form partnerships with families (Willemse, Thompson, Vanderlinde, & Mutton, 2018).…”
Section: Engaging Parents In Schoolsmentioning
confidence: 99%
See 3 more Smart Citations